2016
DOI: 10.1177/1087057115617456
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of NF-κB Signaling as a Therapeutic Target in Autoimmunity

Abstract: Autoimmune diseases arise from the loss of tolerance to endogenous self-antigens, resulting in a heterogeneous range of chronic conditions that cause considerable morbidity and mortality worldwide. In Western countries, over 5% of the population is affected by some form of autoimmune disease, with enhanced or inappropriate activation of nuclear factor (NF)–κB implicated in a number of these conditions. Although treatment strategies for autoimmunity have improved significantly in recent years, current therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
99
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 221 publications
(276 reference statements)
0
99
0
3
Order By: Relevance
“…[345] Activated IκB kinase β (IKKβ) phosphorylates the inhibitor of NF-κB (IκB), which binds NF-κB to inhibit its function, leading to the degradation of IκB and free of NF-κB entering into the nucleus where it activates various target genes. [678] IKKβ can also phosphorylate p53, which is a critical tumor suppressor that activates lots of genes including p21, Bax, and Puma at the transcriptional level, promoting its degradation by β-TrCP. [9] Loss of IKKβ activity increases the stability of p53 and expression of p21 resulting in cell cycle arrest and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…[345] Activated IκB kinase β (IKKβ) phosphorylates the inhibitor of NF-κB (IκB), which binds NF-κB to inhibit its function, leading to the degradation of IκB and free of NF-κB entering into the nucleus where it activates various target genes. [678] IKKβ can also phosphorylate p53, which is a critical tumor suppressor that activates lots of genes including p21, Bax, and Puma at the transcriptional level, promoting its degradation by β-TrCP. [9] Loss of IKKβ activity increases the stability of p53 and expression of p21 resulting in cell cycle arrest and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Impairment in CCDC22 expression, due to rs2204020 SNP located in the 3’ UTR, may dysregulate NF-kB signalling [5], thus contributing to the inflammatory process in SLE. NF-kB is a master regulator of the immune response and its enhanced or inappropriate activation has been shown to be involved in several autoimmune diseases, including SLE [54,55]. In SLE, there is an increased production of autoantibodies by polyclonal activation of B cells, which may be maintained by the inducible transcription factor NF-kBp65 [56].…”
Section: Discussionmentioning
confidence: 99%
“…In SLE, there is an increased production of autoantibodies by polyclonal activation of B cells, which may be maintained by the inducible transcription factor NF-kBp65 [56]. NF-kB therapeutic modulation, through ubiquitination and degradation of individual subunits of this transcription factor, may represent an attractive approach in combatting autoimmune diseases [55]. …”
Section: Discussionmentioning
confidence: 99%
“…NF-kB-mediated dysregulation has been shown to be crucial for the development of numerous pathological conditions beyond inflammation and/or autoimmunity: from AIDS and atherosclerosis to cancer and muscular dystrophy. Therefore, the signaling cascade involving NF-kB has been considered a primary target for pharmacological intervention [6668] and a wide range of drugs targeting crucial steps of this pathway, such as kinases activation, phosphatase enzymatic activity, ubiquitination, nuclear translocation, DNA binding and post translational modifications, have been tested [67, 69]. …”
Section: Targeting the Nf-kb Pathwaymentioning
confidence: 99%
“…Bortezomib (trade name Velcade®) has been the first proteasome inhibitor approved for the clinical treatment of multiple myeloma [67, 69]. Moreover, preclinical studies in murine models of lupus nephritis, colitis, MS and myasthenia gravis have shown bortezomib efficacy [7276].…”
Section: Targeting the Nf-kb Pathwaymentioning
confidence: 99%